Efektivitas Implementasi Pembelajaran di Masa Pandemi Covid-19 bagi Peserta Didik (Studi Kasus di MTs Al-Washliyah Bangun Purba) - Nur Sya'adah Br. Ginting; Siti Rianti Rizki Utami; Abu Hasan Al-Ashari; Rizkan Ma'ruf; Muhammad Hidayat; Fachruddin Azmi; Amiruddin Amiruddin (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
This study aims to describe how the process and implementation of learning during the Covid-19 pandemic for students at MTs Al-Washliyah Bangun Purba. This study uses a qualitative method with a case study approach. In this study, the respondents involved in this research were 2 people, consisting of the Principal and Teacher Educators who taught students. Interviews were conducted in a structured manner with several structured questions. The result is that there are many obstacles in the process and implementation of learning during the Covid-19 pandemic.